Biological Studies on Indian Squid, Uroteuthis duvauceli (D' Orbigny) along the Ratnagiri Coast of India - Pawar N.S.; Bhosale B.P.; Metar S.Y.; Nirmale V.H.; Chogale N.D.; Pagarkar, A.U. (Journal of Indian Fisheries Association, 2019)
The Indian squid Uroteuthis duvauceli is the one of the important commercial fishery resources of India and form significant component of cephalopod landings along the Ratnagiri coast. The present study investigated the feeding and reproductive biology of U. duvauceli landed along the Ratnagiri coast. The study found U. duvauceli to be an carnivore with fishes such as pony fish, sole fish, white fish, sardine, ladyfish and dhoma , juveniles of crabs and prawn forming the main food items. Cannabalism was also noted. The piscivorous tendency was more pronounced in adults. Digested and semi digested matter also occurred in considerable quantity. The present study shows occurrence of more ripe females during November and January indicating possible spawning peak during the post monsoon period. The size at first maturity was found to be 86 mm DML for female. The average sex ratio of males and females was found to be 1: 0.6547 for the entire study period. The fecundity of U. duvauceli was found to vary from 2115 to 13238 eggs with an average of 5442 eggs per female.